American Han : a novel - Lee, Lisa (Novelist) (Algonquin Books of Chapel Hill, 2026)
"Growing up in the San Francisco Bay Area in the 1980s, Jane Kim and her brother, Kevin, dutifully embodied the model minority myth as their parents demanded: both stellar tennis players and academically gifted, they worked hard to make their parents proud. Jane went on to law school. Kevin came close to becoming a professional tennis player. But where they started is nowhere near where they have ended up: Jane has stopped going to her law school classes, and Kevin, now a policeman, has become increasingly distant. Their parents, each on their own path toward the elusive American Dream (their mother hell-bent on having the perfect house and the perfect family, their father obsessed with working his way up from one successful business to the next), don't want to see the family unraveling. When Kevin goes missing, no one recognizes his absence as the warning sign it is until it erupts, forcing them all to come to terms with their past and present selves in a country that isn't all it promised it would be."--Provided by publisher.